Algorithmic derivation of CO2 assimilation based on some physiological parameters of tea bushes in North-East India. (August 2018) - Phukan, Manabjyoti; Savapondit, Debojit; Hazra, Anjan; Das, Sauren; Pramanik, Prabhat
Highlights: Tea bushes may assimilate 1243.8–2526.7 kg CO2  ha −1  year −1 from the atmosphere. High-yielding tea absorbed more CO2 than better quality tea-producing cultivar. CO2 assimilation was significantly correlated to physiology of tea bushes. Those physiological parameters might be considered as indicators of CO2 absorption. An algorithm was derived for computing CO2 assimilation using those variables. Abstract: Tea, an evergreen shrub, is commercially cultivated in dense population as bushes in tea gardens. Periodical pruning of tea bushes makes tea plants distinct from other tree plants. Tea bushes have almost constant height throughout their life-time and have more compact canopy as compared to any forest trees. Hence, established methods of elucidating carbon dioxide (CO2 ) absorption in forest trees could not be employed for measuring CO2 assimilation in tea bushes. In this study, CO2 assimilation potentials of a high-yielding tea cultivar and a better quality producing tea cultivar had been periodically measured by closed-chamber method under field condition. Such type of experiment was not conducted before. This study revealed that tea bushes had potential to assimilate 1243.8–2526.7 kg CO2  ha −1  year −1 and the high yielding tea cultivar absorbed significantly higher amount of CO2 as compared to better quality producing tea cultivar. Several physiological parameters namely number of branches, plucking point density, leaf area and stomatal index were positively correlated to the annual CO2 assimilation by tea bushes. Higher CO2 assimilation in high yielding tea cultivars can be attributed to their larger and dense canopy structure due to more branching, higher plucking point density and higher leaf area. An algorithm has been derived for computing CO2 assimilation in tea bushes by considering the above-mentioned variable as indicators. This will enable to determine CO2 assimilation by tea plantation over a large area by measuring the physiological indicators without exercising in-situ experiments.